The role of forceps in current obstetrics: a retrospective study - Agrawal, Megha; Agrawal, Anshul; Priyanka Gupta; Ashish Goyal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Forceps has been an integral part of the obstetrician’s armamentarium. Obstetric forceps was designed to assist extraction of the fetal head and thereby accomplish the delivery of the fetus. In this present day when there is universal concern regarding the alarming rise of cesarean section rates, a better understanding of this instrument will help the patient as well as the obstetrician. Methods: This was a retrospective observational study done over a two-year period. Cases were enrolled in the study after satisfying the inclusion and exclusion criteria. All data compared in terms of age, parity, gestational age, indications, maternal and neonatal outcome. Results: A total of 1150 antenatal cases were delivered out of which 42 cases were delivered by outlet forceps. Incidence of outlet forceps was 3.75%. Mean baby birth weight was 3.07 kg. No maternal mortality and morbidity recorded. Conclusions: Obstetric forceps have a significant place in modern obstetrics as it is a lifesaving procedure for mother and fetus in many situations.